Community-based entrepreneurship and rural development : creating favourable conditions for small businesses in Central Europe - Fink, Mathias, 1945-; Lang, Richard; Loidl, Stephan (New York, NY. : Routledge, 2013)
Includes bibliographical references (p. [223]-234) and index.